Pendugaan Area Kecil untuk Persentase Balita Miskin Tingkat Kabupaten/Kota di Provinsi Papua Tahun 2023 Menggunakan Pendekatan EBLUP dengan Informasi Klaster - Fusur, Alma Rohmah; Ubaidillah, Azka (Politeknik Statistika STIS, 2024)
The development of a country depends on the quality of its human resources. In 2020, Indonesia's Human Capital Index (HCI) is 0.54. This figure is relatively low compared to other Southeast Asian countries. One of the causes of Indonesia's low HCI rate is poverty. In 2022, the highest percentage of poor children is in Papua. In addition, under-five are the highest poor group among other age groups. Direct estimation often results in less precise guesses due to insufficient sample size. Even direct estimation cannot estimated when an area has no sample. This study uses SAE EBLUP method with cluster information to get the estimated percentage of under-five poverty. The results show that 7 districts/cities in Papua Province have a direct estimator RSE of more than 25%. Using cluster analysis, direct estimators with RSE for unsampled areas were produced, and EBLUP estimators with cluster information were proven to be better than direct estimators from the RSE produced lower than the direct estimator RSE.